PEMETAAN TINGKAT RESIKO KERUSAKAN AKIBAT GEMPA BUMI PADA SEKOLAH DASAR DAN MADRASAH IBTIDAIYAH SE-MALANG RAYA MENGGUNAKAN APLIKASI SISTEM INFORMASI GEOGRAFIS - Rusli, Rusli (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2015)
The purpose of this study was to map the risk of earthquake damage at all Elementary Schools and Islamic Elementary Schools in Malang. mapping process using Geographic Information System (GIS). Software used for mapping is ArcView GIS 3.3. Stages in mapping the level of risk the damage caused by the earthquake is to collect data and coordinate address Elementary Schools and Islamic Elementary Schools, the data of the earthquake, the maximum ground acceleration calculation, classification and interpretation. From the calculation results showed that the Elementary Schools and Islamic Elementary Schools is located in the southern Malang has a degree of severe damage to the value of PGA 228878- 234987 gal. While elementary school is located in the north of Malang has a high risk of earthquake is very secure with PGA value 180 009 -186 117 gal.Keywords: earathquake, Malang, Elementary School.